Effects of three feed attractants on the growth performance and meat quality of the largemouth bass (Micropterus salmoides) - Yue, Yuhua; Chen, Mingshi; Bao, Xiaoxue; Yu, Yingying; Shi, Wei; Kumkhong, Suksan; Liu, Yuhong; Yang, Ying; Yu, Hui (Frontiers in Marine Science, 2022)
The trial was conducted to investigate the effects of limonene, allicin and betaine supplementation in low fish meal (FM) diet on growth performance, antioxidant capacity, meat quality and intestinal health in largemouth bass (M. salmoides). The first part was the biting-balls test, which showed that with the increase of the concentration, the attracting effect firstly increased and then decreased and the effect achieved optimized outcomes when the attractants’s concentrations were 0.2% (P < 0.05). The second part was a 9-week feeding trial, M. salmoides was randomly divided into 5 groups (n = 600) and fed with different diet (30% FM diet (FM30), 40% FM diet (FM40), and 30% FM supplemented with 0.2% limonene (FM30 + L), 0.2% allicin (FM30 + A) or 0.2% betaine (FM30 + B) diet). The study showed that M. salmoides grew best at 4th week and had no significant effect at 9th week (P > 0.05). At 9th week, supplementation with limonene, allicin or betaine in FM30 diet has no effect on muscle composition nutritional (P > 0.05) but the content of malondialdehyde in the liver or serum was significantly lower (P < 0.05), and the liver glutathione activity was higher than that of the FM30 group while the catalase or superoxide dismutase activity was lower. Compared with FM30 group, the supplementation with limonene, allicin or betaine diet had higher pH, redness (a*), yellowness (b*) (P > 0.05), and lower refrigeration loss, cooking loss values (P < 0.05). Furthermore, The FM30 + L, FM30 + A and FM30 + B groups had higher values for villus height, lamina propria, crypt depth, submucous layer, and serous layer (P < 0.05) compared to the FM30 group. Taken together, these results indicated that limonene, allicin and betaine had a dose-time effect on M. salmoides, and the optimum concentration of attracting effect was 0.2%. M. salmoides grew best at 4th week and had no significant effect at 9th week but reduced liver and serum oxidative damage and improved meat quality and intestinal health.